Medical surgical complications in the evolution of the palliative oncological patient - Escajadillo-Luck, Arianna Irina (2022)
Cancer patients tend to have a disease course with mostly unfavorable progressive evolution that often leads to death, and these episodes are made up of the medical-surgical complications associated with the underlying disease. In addition to that they are usually distressing for the family and the patient himself. It is therefore important to establish the appropriate therapeutic objectives (adequacy of the therapeutic effort) to improve the management according to the evolution of the disease and the complications that it may present, which are potentially fatal. This approach is given by palliative care that seeks to improve the quality of life of the patient and family through the treatment of pain and other physical, social, psychological and spiritual problems. Being fully compatible with curative measures.Then, in this document, it has been succinctly exposed regarding 4 life- threatening complications such as: massive hemorrhages, seizures, spinal compression syndrome and malignant intestinal obstruction and their management according to the palliative care approach.